Kualitas Sumber Daya Aparatur Dalam Mencapai Tujuan Pembagunan Di Distrik Yamo, Kabupaten Puncak Jaya Provinsi Papua - Yoma, Mesina; Pratiknjo, Maria H; Lake, Femmy (JURNAL ILMIAH SOCIETY, 2016)
Implementation of development in the district of Puncak Jaya regency Yamo still found the existence of some constraints affecting the effectiveness of work among employees. Constraints in question concerns the improvement of the quality of personnel resources that are not optimal so that needs to be improved through education, training and staffing in order to perceive the efforts made in the quality of personnel resources to achieve development goals Yamo District of Puncak Jaya. Type of study used a descriptive study using informants determination by purposive sampling, and data collection techniques done in the form of interviews, and literature. Data analysis techniques used qualitatively to make the transcript then arranged in a matrix form and then analyzed using content analysis method of data reduction. The results showed that the quality of personnel resources on civil servants in the District Yamo Puncak Jaya regency is very low resulting in productivity did not correspond with the expectations of society that need special attention from the local government through the development of education, training, and placement of the right employees to improve the quality of the source human.